MUHAMMAD ASAD’S POLITICAL THEORY REVISITED: Epistemological Review on Contemporary Islamic Politics in Global South - Nabil, Ahmad Amir (Epistemé: Jurnal Pengembangan Ilmu Keislaman, 2024)
The article examines Muhammad Asad’s epistemological ground, reflected in his works on the principle of Islamic governance and its basic constitution and foundational structure. In this regard, he formulated the constitutional ideas of the Islamic state, whose constitution contains the provision of Islamic law that practices and implements the norms and postulates of the Divine Writ. This idea was partly enshrined in some of Global South constitutional law, whose political establishment was formed in 1947. It essentially discussed Muhammad Asad’s political ideas and their underlying philosophy as espoused in his works. The work was conducted using qualitative approaches to library research. The data were analyzed using descriptive, analytical, and comparative techniques. The finding shows that Muhammad Asad had formulated a comprehensive theoretical framework of the legal aspect of Islamic governance drawn up from the fundamental principle and doctrine of the sharia and its moral norms deriving from the Qur’anic and the sunnah bases while advocating democratic ideals and principles based on conventional practice and requirement of the modern context of the nation-state.